Propiedades Piezoeléctricas del Pentóxido de Niobio y Pentóxido de Tantalio: un estudio desde primeros principios (2017)
ABSTRACT: Nb2O5 and Ta2O5 are wide-bandgap semiconductor oxides that have attracted great interest in recent years due to their technological applications, such as in electronics, telecommunications or photocatalysis. Because of this, we present a study based on first-principles calculations of the piezoelectric properties of the Z and β phases of Ta2O5 as well as the Z and P phases of Nb2O5 by using the Density Functional Theory and the Generalized Gradient Approximation with PBEsol parameterization. Once the equilibrium geometry was determined for each of these phases, we made a calculation using the linear response theory to determine the piezoelectric tensor associated with each phase. We discovered that the Z phase of both compounds presents good piezoelectric response. Additionally, β-Ta2O5 does not show such response.